Effects of In, Al and Sn dopants on the structural and optical properties of ZnO thin films - Caglar, Yasemin; Ilican, Saliha; Caglar, Mujdat; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2007)
Effect of In, Al and Sn dopants on the optical and structural properties of ZnO thin films have been investigated by X-ray diffraction technique and optical characterization method. X-ray diffraction patterns confirm that the films have polycrystalline nature. The thin films have (002) as the preferred orientation. This (0 0 2) preferred orientation is due to the minimal surface energy which the hexagonal structure, c-plane to the ZnO crystallites, corresponds to the densest packed plane. The grain size values of the films are found to be 29.0, 35.2 and 39.5 nm for In, Al and Sn doped ZnO thin films, respectively. The optical band gaps of the films were calculated. The absorption edge shifts to the lower wavelengths with In, Al and Sn dopants. The inclusion of dopant into films expands also width of localized states as E-UIn > E-UA1 > E-USn. The refractive index dispersion curves obey the single oscillator model. The dispersion parameters and optical constants of the films were determined. These parameters changed with In, Al and Sn dopants. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ZnO thin film; optical constant; refractive index; localized states